The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.pss.2010.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional time-dependent model of the transport of minor species in the Venus night side upper atmosphere

Abstract: a b s t r a c tWe present a numerical tool developed to quantify the role of processes controlling the spatio-temporal distribution of the NO ultraviolet and O 2 ð 1 D g Þ infrared nightglows in the Venus night side upper atmosphere, observed with the VIRTIS and SPICAV instruments on board Venus Express. This numerical tool consists in a two-dimensional chemical-transport time-dependent model which computes in a hypothetical rectangular solving domain the spatio-temporal distributions of the number densities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In all profiles analyzed, no correlation has been found between the presence of multiple peaks in the NO and O 2 emissions. This is in perfect agreement with Gérard et al (2009a) and Collet et al (2010) who both described the lack of correlation between the two emission peaks.…”
Section: Multiple Peakssupporting
confidence: 92%
See 1 more Smart Citation
“…In all profiles analyzed, no correlation has been found between the presence of multiple peaks in the NO and O 2 emissions. This is in perfect agreement with Gérard et al (2009a) and Collet et al (2010) who both described the lack of correlation between the two emission peaks.…”
Section: Multiple Peakssupporting
confidence: 92%
“…This intensity is too bright and peaks 6 km above those derived from VIRTIS observations (Gérard et al, 2009b;Soret et al, 2012). The distance between the two peaks of NO and O 2 emissions was discussed in Collet et al (2010) and Brecht et al (2011). They both modeled a distance smaller than determined from observations.…”
Section: One-dimensional Modelingmentioning
confidence: 88%
“…7 sketches the downward transport of atoms that recombine and generate airglow layers in different altitude regimes. The two-dimensional transport model by Collet et al (2010) reproduced the separation between the NO and O 2 (a 1 D) emissions following localized injection of a blob of O and N atoms. It is a consequence of the coupling between the horizontal and vertical transport processes.…”
Section: Publicationsmentioning
confidence: 96%
“…Furthermore, Gérard et al [2009b] have shown the first concurrent observations of the O 2 IR and NO UV night airglow with VIRTIS and SPICAV data. They concluded that the two nightglow emissions are not spatially correlated, giving rise to the idea that each emission is controlled by different dynamical processes [ Collet et al , 2010]. Recent publications [ Gérard et al , 2008b, 2008c, 2009a, 2009b, 2010; Bertaux et al , 2007; Piccioni et al , 2009] detailing observations made by these instruments are discussed in section 4.…”
Section: Introductionmentioning
confidence: 99%